Vehicle Trajectory Analysis on the Effect of Additional Load Distribution Disturbance at Different Speeds for Collision Avoidance Systems - Mohamad Heerwan bin Peeie; Abdullah bin Zulkifli; Muhammad Izhar bin Ishak (Automotive Experiences)
Collision avoidance (CA) systems have become a requirement in vehicles due to their ability to prevent collisions. Despite the implementation of these systems on the road, accidents still happen due to the lack of adaptability of CA systems corresponding to road environment nonlinearities and external disturbances. Hence, this research focuses on the effect of external disturbances, such as additional load distribution on the vehicle while avoiding obstacles. The deployment of the CA scenario, considering the presence of disturbance, was simulated in MATLAB Simulink, with the reference trajectory for the system obtained from a skilled driver in real-time experiments at different speeds. The objective of this study is to observe and analyse the effect of additional load disturbances on vehicle stability, especially when the driver countersteers to avoid an obstacle. An increase in the additional load percentage at each side of the vehicle produces excessive lateral force opposite to the direction of the vehicle. This scenario creates a significant load transfer phenomenon and directly causes the vehicle to oversteer and understeer while avoiding obstacles. It has been observed that human cognition plays a huge role in defining a reference trajectory at different speeds while avoiding an obstacle. The pattern of the reference trajectory also affects the magnitude of the load transfer phenomena, especially when the driver manoeuvres the vehicle aggressively.